Literatura chorwacka i jej polscy ambasadorzy. Uwagi do bibliografii przekładów literatury chorwackiej w Polsce w latach 2007—2013 - Majdzik, Katarzyna (Przekłady Literatur Słowiańskich, 2014)
Croatian Literature and its Polish Ambassadors. Comments on the Bibliography of Translations of Croatian Literature in Poland (2007—2013) The article based on the bibliography of translations of Croatian literature in Poland from 2007 to 2013 discusses the role of translators and editors in the crosscultural and interliterature communication. During that period several texts` compilations and anthologies of Croatian literature (mostly the latest) has been published in Poland. The mentioned books are the results of the Polish‑Croatian cooperation of writers, translators as well as researchers (e.g. [1] the selection of Miro Gavran’s works or [2] the project entitled Kroatywni that involved Croatian and Polish researchers) or, on the contrary, they are result of independent work of one translator (e.g. the anthology of Croatian poetry by G. Łatuszyński). Investigating diverse anthologies of Croatian literature printed in Poland and Croatia from 2007 till 2013 the question of the literary canon and the difference between the idea of the literature in the original and target culture are risen. Key words: bibliography, translation, croatian literature, translator, anthology, canon.